Addressing the Stigma and Size of Antiretroviral (ARV) Tablets: A Call for Innovation - Willie, Michael Mncedisi (Advances in Healthcare Research, 2025)
Purpose: This study investigates how antiretroviral (ARV) tablet size affects medication adherence, particularly in individuals with dysphagia, pediatric populations, and the elderly. It highlights the role of tablet size in influencing adherence and its broader impact on virological control, drug resistance, and HIV-related morbidity. Research Method: This research employed a constructivist paradigm, conducting a scoping literature review to explore existing studies. Systematic inclusion and exclusion criteria were applied to select relevant sources. Thematic analysis identified key patterns and refined central themes to ensure analytical consistency regarding ARV tablet size and associated adherence barriers. Results and Discussion: The review reveals that smaller tablets, particularly in dolutegravir-based regimens, significantly enhance adherence by reducing the physical difficulty of swallowing. However, the visibility of medication continues to contribute to stigma, potentially undermining adherence. Emerging innovations, such as mini-tablets, nanotechnology, and long-acting injectables, show promise; however, their cost and limited availability hinder widespread adoption in low-resource settings. Implications: The findings suggest a need for patient-centred ARV formulations that reduce stigma and improve access. Policymakers and pharmaceutical stakeholders are encouraged to develop smaller, affordable ARV options to support better adherence and long-term treatment success.